The business case for corporate governance / edited by Ken Rushton. - Rushton, Ken (Law practitioner series., 2008)
This book goes beyond the 'what and how' of corporate governance to explore the impact and benefits of good governance for companies and their investors. The contributors are leading market practitioners, investors, academics and consultants who offer their own views based on a wealth of experience. Topics covered include what makes for an effective board and is the unitary board sustainable? The contribution of governance to financial performance - is the research conclusive? Managing risk and reputation - how do boards ensure they are trusted by their shareholders? The benefits of market led standard setting -do US and EU regulatory initiatives threaten the traditional UK approach? The book looks to dispel the belief that governance is a burden on companies that adds little value by demonstrating the contribution it makes to board effectiveness and corporate performance.